A Novel of Floating Delivery System is a Tool to Enhance Absorption of Drug: A Review - Iyan Sopyan (Indonesian Journal of Pharmaceutics, 2020)
This assessment of a floating drug for a novel of new drug delivery system (NDDS) is written to elucidate FDDS based on existing literature. The most recent progresses of FDDS include the formulation and physiological variables that could affect gastric retention and formulations are discussed in detail. This review also summarizes method assessments for FDDS pharmaceutical dosage form and its classification. FDDS. FDDS is made to increase the absorption of the drug that is expected to dissolve in the stomach so that the drug enters the intestine in a dissolved state and the fraction of the absorbed drug increases. FDDS approach is the best way to deal with drugs with low solubility in the digestive tract.Keywords : Floating Tablet, Evaluation, Gastric Retentive